Stacked Bt maize and arthropod predators: exposure to insecticidal Cry proteins and potential hazards - Svobodová, Zdeňka; Shu, Yinghua; Skoková Habuštová, Oxana; Romeis, Jörg; Meissle, Michael (Proceedings - Royal Society. Biological sciences, 2017)
Genetically engineered (GE) crops with stacked insecticidal traits expose arthropods to multiple Cry proteins fromBacillus thuringiensis(Bt). One concern is that the different Cry proteins may interact and lead to unexpected adverse effects on non-target species. Bi- and tri-trophic experiments with SmartStax maize, herbivorous spider mites (Tetranychus urticae), aphids (Rhopalosiphum padi), predatory spiders (Phylloneta impressa), ladybeetles (Harmonia axyridis) and lacewings (Chrysoperla carnea) were conducted. Cry1A.105, Cry1F, Cry3Bb1 and Cry34Ab1 moved in a similar pattern through the arthropod food chain. By contrast, Cry2Ab2 had highest concentrations in maize leaves, but lowest in pollen, and lowest acquisition rates by herbivores and predators. While spider mites contained Cry protein concentrations exceeding the values in leaves (except Cry2Ab2), aphids contained only traces of some Cry protein. Predators contained lower concentrations than their food. Among the different predators, ladybeetle larvae showed higher concentrations than lacewing larvae and juvenile spiders. Acute effects of SmartStax maize on predator survival, development and weight were not observed. The study thus provides evidence that the different Cry proteins do not interact in a way that poses a risk to the investigated non-target species under controlled laboratory conditions.
Keywords: hemolyziny; larva; potravní řetězec; Bacterial Proteins; Arthropods; členovci; geneticky modifikované rostliny; Hemolysin Proteins; Plants, Genetically Modified; kukuřice setá; zvířata; bakteriální proteiny; endotoxiny; Animals; Larva; Bacillus thuringiensis; Food Chain; Endotoxins; Zea mays